The Impact of Publicly Funded Research Education: A Systematic Literature Review - Cecille T Godin (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study aims to examine how the outcomes and effectiveness of publicly funded research in education are assessed by reviewing existing literature. It focuses on how research outputs are translated into educational practice, policy, and institutional improvement, with the goal of informing decision-making, strengthening research utilization, and guiding future studies in education. Methodology: A systematic review methodology was employed to analyze published studies on publicly funded educational research. Relevant literature was retrieved from Google Scholar and organized using EndNote. The PRISMA framework guided the study selection process, resulting in 18 publications from 2000 to 2023. Thematic analysis was used to examine how studies assess research utilization, knowledge transfer, and outcome evaluation in educational settings. Main Findings: The review identified two main themes: (1) Assessment of Knowledge Translation and Research Utilization, which focuses on how research findings are evaluated in terms of their application in educational practice and decision-making; and (2) Evaluation of Funding Priorities and Research Outcomes, which highlights how funding structures influence research productivity, dissemination, and measurable educational outcomes. Overall, the findings show that publicly funded research contributes to educational improvement when supported by clear mechanisms for evaluating knowledge use, collaboration, and institutional change. Novelty/Originality of this study: This study is novel in that it integrates research impact frameworks with educational evaluation theories to systematically examine how publicly funded research in education is assessed and translated into measurable outcomes. It is original in shifting the focus from general discussions of research impact to a structured analysis of evaluation processes, thereby addressing a key gap in how educational research effectiveness is conceptualized and measured.